Tracking reaction dynamics in solution by pump–probe X-ray absorption spectroscopy and X-ray liquidography (solution scattering). Issue 19 (19th January 2016) - Kim, Jeongho; Kim, Kyung Hwan; Oang, Key Young; Lee, Jae Hyuk; Hong, Kiryong; Cho, Hana; Huse, Nils; Schoenlein, Robert W.; Kim, Tae Kyu; Ihee, Hyotcherl
Abstract : TRXL and TRXAS are powerful techniques for real-time probing of structural and electronic dynamics of photoinduced reactions in solution phase. Abstract : Characterization of transient molecular structures formed during chemical and biological processes is essential for understanding their mechanisms and functions. Over the last decade, time-resolved X-ray liquidography (TRXL) and time-resolved X-ray absorption spectroscopy (TRXAS) have emerged as powerful techniques for molecular and electronic structural analysis of photoinduced reactions in the solution phase. Both techniques make use of a pump–probe scheme that consists of (1) an optical pump pulse to initiate a photoinduced process and (2) an X-ray probe pulse to monitor changes in the molecular structure as a function of time delay between pump and probe pulses. TRXL is sensitive to changes in the global molecular structure and therefore can be used to elucidate structural changes of reacting solute molecules as well as the collective response of solvent molecules. On the other hand, TRXAS can be used to probe changes in both local geometrical and electronic structures of specific X-ray-absorbing atoms due to the element-specific nature of core-level transitions. These techniques are complementary to each other and a combination of the two methods will enhance the capability of accurately obtaining structural changes induced by photoexcitation. Here we review the principles of TRXL and TRXAS and present recent application examples of the two methods for studying chemical and biological processes in solution. Furthermore, we briefly discuss the prospect of using X-ray free electron lasers for the two techniques, which will allow us to keep track of structural dynamics on femtosecond time scales in various solution-phase molecular reactions.